2022
DOI: 10.3389/fnut.2022.799127
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Moringa oleifera in Two Independents Formulation and as Neuroprotective Agent Against Scopolamine-Induced Memory Impairment in Mice

Abstract: BackgroundThe cognitive deficit has frequently been found in the elderly population. Several studies have shown that every single part of Moringa oleifera, including leaves, roots, and seeds, has abundant micronutrients, such as flavonoids, which improve the neurobehavioral capacity. However, herb parts that display optimal neuropharmacological properties remain unknown.ObjectiveWe investigate whether M. oleifera seed oil (MOO) or aqueous M. oleifera leaves extracts (MOEs) may ameliorate memory impairment in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…In our previous study, 26 we have reported that palmitic acid, oleic acid, stearic acid, stigmasterol, and β sitosterol were abundant on the seed oil from MO (MOO), and confirmed the neuroprotective effects of MOO by improved the memory impairment caused by scopolamine injection through the inhibition of AChE activity and overexpression of NF-κB protein level, and modulate the level of Trk-B expression. Similarly, the administration of 70% ethanol extract of MO seeds could improve memory and cognitive impairment in scopolamine mice model.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…In our previous study, 26 we have reported that palmitic acid, oleic acid, stearic acid, stigmasterol, and β sitosterol were abundant on the seed oil from MO (MOO), and confirmed the neuroprotective effects of MOO by improved the memory impairment caused by scopolamine injection through the inhibition of AChE activity and overexpression of NF-κB protein level, and modulate the level of Trk-B expression. Similarly, the administration of 70% ethanol extract of MO seeds could improve memory and cognitive impairment in scopolamine mice model.…”
Section: Introductionmentioning
confidence: 56%
“…24 Moreover, long-term consumption of MO progressively increases the body weight after the 12 weeks, improved spatial and non-spatial memory performance, protect against oxidative stress, inhibit AChE activity and suppresses neuronal degeneration in the hippocampus of rats. 25 In our previous study, 26 we have reported that palmitic acid, oleic acid, stearic acid, stigmasterol, and β sitosterol were abundant on the seed oil from MO (MOO), and confirmed the neuroprotective effects of MOO by improved the memory impairment caused by scopolamine injection through the inhibition of AChE activity and overexpression of NF-κB protein level, and modulate the level of Trk-B expression. Similarly, the administration of 70% ethanol extract of MO seeds could improve memory and cognitive impairment in scopolamine mice model.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Lamoub, et al report this aqueous extract of Moringa oleifera also increases the activity of antioxidant enzymes and reduces levels of malondialdehyde in the blood [28]. Our previous study found MOW has a compound of triterpenoid, polyphenolic, saponin, tannin, flavonoid, alkaloid and anthraquinone [11]. Flavonoid is a secondary metabolite that can activate antioxidant enzymes and reduce lipid peroxidation [29].…”
Section: Effect Of Mow On Oxidative Stress Parametersmentioning
confidence: 96%
“…Moringa oleifera leaves are enriched in phytochemicals such as tannins, sterols, saponins, terpenoids, phenolics, alkaloids, and flavonoids [7]. Previous rodent studies found that extracts of Moringa oleifera leaves have anxiolytic and antiepileptic properties [8,9], antidepressant [10], and improves memory [11].…”
Section: Introductionmentioning
confidence: 99%